“We’re less noticeable to people”: Centering Tween Girl Activist Citizenship - Bernier, Alexe (Atlantis)

(untitled) (Mount Saint Vincent University, 2024)
In recent years, there has been significant attention paid to girls who are engaged in activism. When we look at who has been recognized for their activism, however, mainstream exposure to girl activists has primarily included teenagers and youth. Girls of the tweenhood age, for example, are also engaged in activism but their efforts go largely unnoticed or face patronization. Instead of being taken seriously, the activism of many tween girls is: (1) clouded by the constructed inherent innocence of childhood, (2) entangled with the construction of (white) tween girlhood as a time of frivolity and fun, and (3) marginalized due to the adult-centric nature of citizenship in Canada and the United States. As the very structures that would traditionally allow for adults to make their voices heard are not designed for the equitable participation of children, tween girls are required to participate in creative ways. This article, therefore, frames tween girls’ activism as citizenship and offers opportunities to both reconsider and validate these varied activist practices as legitimate democratic participation. Tween girls are already shaping their social, cultural, and political worlds, asserting that they belong and deserve to be seen, heard, and taken seriously. The lenses of societal and feminist responses need to be reoriented and refocused to see it.